PENGUATAN KESADARAN KRITIS SEJAK DINI MELALUI KURIKULUM SD BERBASIS TEORI REVOLUSI SOSIAL - Alisa Marta Boimau; Fridarina Taneo; Windi Natonis; Resin Tefa; Maria Indriani Sesfao (JIP: Jurnal Ilmu Pendidikan, 2025)
Critical awareness is an important foundation in forming a generation that is able to think independently, care about social reality, and dare to voice change. Unfortunately, elementary school (SD) education in Indonesia still tends to emphasize memorization and obedience, and not reflective thinking. This journal highlights the importance of instilling critical awareness from an early age through the elementary school (SD) curriculum, by referring to the theory of social revolution as a conceptual framework. This theory emphasizes the importance of structural change in society that can start from changing the way each individual thinks from an early age. In this context, the elementary school (SD) curriculum needs to be directed to not only teach basic knowledge, but also help shape students' character so that they are able to identify injustice, understand social reality, and develop a critical attitude towards their surroundings. With a dialogic, contextual, and participatory learning approach, elementary schools (SD) can be an initial space for the growth of children's critical awareness. This journal offers realistic ideas and implementation strategies so that the elementary school (SD) curriculum can be part of an effort to create long-term social change through transformative education.